2015
DOI: 10.1039/c5ra19676k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aggregation behavior and phenolic hydroxyl group content on the performance of lignosulfonate doped PEDOT as a hole extraction layer in polymer solar cells

Abstract: †Electronic Supplementary Information (ESI) available: [the results including SEM images of various block-like self-assemblies from LS and ALS; DLS measurement of LS solution and ALS solution in H2O/EtOH (v/v, 1/3); Proposed schematic for the polymerization of EDOT in the presence of LS and ALS; UV absorption spectra of PEDOT:LS and PEDOT:ALS aqueous dispersion]. SeeUsing lignosulfonate (LS) and alkyl chain-coupled lignosulfonate-based polymer (ALS) as raw material, the aggregation behavior of LS and ALS was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…(A) Lignin and its derivatives in DSSCs: (i) modified lignophenols as photosensitizer, and (ii) lignin‐derived carbon electrode. (B) Lignin/conductive polymer as a HTL in perovskite solar cells: (i) device architecture, (ii) energy‐level diagram, and (iii) proposed electron‐transfer process of lignin‐based HTL: PEDOT:LS (up) and PEDOT:ALS (down) . (iii) Reproduced with permission .…”
Section: Lignin‐based Materials For Energy‐conversion Applicationsmentioning
confidence: 99%
“…(A) Lignin and its derivatives in DSSCs: (i) modified lignophenols as photosensitizer, and (ii) lignin‐derived carbon electrode. (B) Lignin/conductive polymer as a HTL in perovskite solar cells: (i) device architecture, (ii) energy‐level diagram, and (iii) proposed electron‐transfer process of lignin‐based HTL: PEDOT:LS (up) and PEDOT:ALS (down) . (iii) Reproduced with permission .…”
Section: Lignin‐based Materials For Energy‐conversion Applicationsmentioning
confidence: 99%
“…Block-like aggregation behavior was more dominant in ASL compared to SL due to cross-linked alkyl chain polymerization in SL. Based on the aggregation behavior and electron transport characteristics of the SL and ASL, the materials have been applied as dopants to improve the conductivity of PEDOT [ 109 ]. The power conversion efficiency of polymer solar cell also depends on the aggregation behavior of the dopants that is ultimately affected by the hydroxyl group content [ 105 , 109 ].…”
Section: Overview Of Carbon-based Materials In Photocatalysis and Phomentioning
confidence: 99%
“…The results of the study also showed that hydroxyl group content is directly related to the hole mobility and PCE, whereas increase in hydroxyl group increased hole transport ability and PCEs and vice versa. Furthermore, the high pH of SL and ASL is an advantage of the conductive polymers over conventional dopant PSS that will prevent corrosion of ITO layers [ 109 ].…”
Section: Overview Of Carbon-based Materials In Photocatalysis and Phomentioning
confidence: 99%
“…So far the charge carrier transport characteristics in organic semiconductors have been usually analyzed by several techniques, such as time of ight (TOF), 9,10 transient electroluminescence (TEL), 11,12 space charge limited current (SCLC) [13][14][15] and admittance spectroscopy (AS). [16][17][18][19][20][21] In these techniques, notably, AS has been shown to be a feasible and powerful tool to explore the charge carrier transport kinetics and relaxation processes and involved in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%